Upaya Pengembangan Karakter Tanggung Jawab Siswa Sekolah Dasar Melalui Media Jurnal Tiga Kata Ajaib - Andriyati, Shinta; Amalia, Arsyi Rizqia; Sutisnawati, Astri (Jurnal Gentala Pendidikan Dasar, 2023)
The research carried out aims to develop students' responsible character in implementing learning through the three magic words journal media. The research was carried out at SDN Babakansitu, Sukabumi district from December to March. The research implemented was using Classroom Action Research (PTK). The subjects involved in this research were 15 grade III students at SDN Babakansitu. Data collection techniques in this research include observation, interviews, field notes and documentation. Through journal media the three magic words, character not quite enough answer students develop and achieve as much as 91.3% in the very good category. That shows that use media journal three magic words proven to improve development character not quite enough answer students in class low.